Consulting report – Natura Cosméticos SA - Capcha Rivera, Cinthia Enedina (2017)
Natura S.A is a Brazilian company that sells beauty products and personal care through direct sales. Currently it has a greater presence in the Latin American market: Brazil, Argentina, Mexico, Peru Colombia and Chile. On the other hand, Atento is a Peruvian company that provides the services of the contact center for all operations of Natura Latin America, without including Brazil. The main problem identified is the inefficient management of the contact center by Natura which is deteriorating the quality of the service. The inefficiencies are related to the lack of quality tools, limited definition of indicators, poor staff management, and poor added value during the call service. In this sense, the Regional Customer service area (Natura) is interested in look for better processes and indicators for the management of the contact center in order to find a model that optimizes the control of the performance of the supplier. The literature reviewed to develop the solution is about quality management systems, contact center outsourcing models, methods to add value to services, and process improvement methodologies. After that, three alternatives were developed where each of one was evaluated according factor of costs, innovation, risk, value added, feasibility and feedback of Natura. The final proposal has two phases, the first one is to implement Business Intelligence in which it will be possible to analyze the database of the calls in order to develop initiatives of improvement in short and long term, as the reduction of unwanted calls. After that, in order to complement the business intelligence proposal, the second phase will be the implementation of the value-added strategy in which it will look for higher quality and personalization of call service according to the profile of the consultants per country. The implementation plan implies an active participation of both parties. Finally, the investment to implement this proposal is 68,300 PEN and the expected benefits are reduction of expenses of 750,000 PEN, process optimization and improvement of consultant’s satisfaction.